FACTOR ANALYSIS OF INTRANATAL AND POSTNATAL TOWARD STUNTING - Nur Chabibah; Rini Kristiyanti; Milatun Khanifah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
Multidimensional factors caused stunting and intervention, mostly focusing on the first 1000 days of life. Maternal factors consist of prenatal, intranatal, and postnatal factors. The purpose of this study was to determine the intranatal and postnatal factors influencing the incidence of stunting. The design of this research was descriptive-analytic with a retrospectives approach. This study's population was children aged 1-3 years old using random cluster sampling and obtained 35 respondents as case group and 35 respondents as the control group. This study shows that there were variables associated with stunting such as labour history with odds ratio 0.103 (p-value: 0.001; 95% CI: 0.030-0.350) and basic immunization history with odds ratio 5.785 (p-value: 0.022; 95% CI: 1.285-26.028). Based on the finding, comprehensive health care is needed in preventing stunting Keyword: Stunting, Intranatal, Postnatal, Labor history, Basic immunization history